Unprecedented pressure-driven metallization and topological charge transport in an anion radical salt - Sudeshna, Samanta; Nissimagoudar, Arun S.; Basori, Rabaya; Kuzmin, Alexei; Li, Mingtao; Zhang, Jinbo; Wang, Lin; Tian, Yongjun; Mao, Ho-kwang (Elsevier, 2021)
The hybrid inorganic/organic closed -stacking and soft lattice of a copper anion radial (Copper-7,7,8,8-tetracyanoquinodimethane) renders its electrical conductivity and structural modifications, which are susceptible to temperature and pressure. The geometry of its metal-ligand construction contemplates the concept of topology with a charge-transfer instability. A pressure-induced ionic-neutral phase transition occurs and accompanies an anomalously large electrical conductivity, carries topological charges, and possesses a low energy gap smaller than the Coulomb gap. X-ray absorption spectroscopy of the metal establishes the high electrical conduction by the topological charges. X-ray diffraction and the first-principles calculations further suggest that the compression leads to an irreversible alteration in the metal coordination and rotation of the quinoid rings of the anion. The present observation demonstrates a close coupling of topological charges and lattice dynamics within a relatively low-pressure regime, which may expand a novel paradigm for the comprehensive topological charge transport phenomena including thermoelectric effects in future.--//-- This is the preprint version of the following article: Sudeshna Samanta, Arun S. Nissimagoudar, Rabaya Basori, Alexei Kuzmin, Mingtao Li, Jinbo Zhang, Lin Wang, Yongjun Tian, Ho-kwang Mao, Unprecedented pressure-driven metallization and topological charge transport in an anion radical salt, Materials Today Physics, Volume 20, 2021,100467, ISSN 2542-5293, https://doi.org/10.1016/j.mtphys.2021.100467. (https://www.sciencedirect.com/science/article/pii/S2542529321001280).This work is licensed under a CC BY-NC-ND license.
We thank Kiyofumi Nitta and Oki Sekizawa for providing assistance on the setup for XAFS measurements under proposal No. 2018A1760 at BL05XU, Spring-8, Japan.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Topological charge transport; pressure-temperature phase-diagram; x- ray absorption; charge-transfer complex